Menilai Islamisme, Pembangunan Perdamaian, dan Dialog Antariman di Papua, Indonesia - Ridwan; Khotimah, Husnul (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
This article describes and analyses a complex relationship between Islamisation, peacebuilding, and interfaith dialogue in Papua. Before the presence of transnational Islam, the relationship between Muslims and Christians was in harmony, and they lived peacefully. However, such radical transnational Islamic groups have created tensions and conflict between these two religions as well as intra-religious frictions among Islamic groups. Furthermore, tensions among different religions have provided another nuance to the long-running separatism-flavoured conflict in Papua. This paper will describe the presence of transnational groups that promote Islamism and how the religious leaders in Papua, through Forum Kerukunan Umat Beragama or FKUB [the Religious Forum for Tolerance], reduce religious conflicts by making Deklarasi Papua Tanah Damai [Papua Land of Peace Declaration]. Furthermore, it explicates the framework of interfaith dialogue and how it is practised to maintain communal harmony in Papua. However, the interfaith dialogue is still used traditionally in Papua and has yet to resolve the root cause of the existing religious conflicts.  Keywords: Islamisation, Communal Conflict, Transnational Islam, Peacebuilding, Interfaith Dialogue